THE INFLUENCE OF VIDEO MEDIA AND POWER POINT UTILITIES TO THE LEARNING INDEPENDENCE ON ISLAMIC EDUCATION SUBJECT AT SINJAI SENIOR HIGH SCHOOL - Munawaroh Munawaroh; Ilyas Ismail; Muh. Rusdi Rasyid (Universitas Islam Negeri Alauddin Makassar, 2022)
This research was ex post facto applying a quantitative methodological approach and a scientific approach in psychology. There were 61 Respondents in this study obtained by proportional cluster random sampling and collected through a questionnaire. The instrument was analyzed using descriptive and inferential statistics. The statistical hypothesis testing results from F_count analysis of 0.025 and p-value = 0.000 <0.05 means that H_0 is rejected and H_a is accepted. It indicated an effect of students' perceptions on utilizing video and PowerPoint media with students' independent learning in PAI subjects in class XI SMA Negeri 6 Sinjai. It means a simultaneous (simultaneous) influence on students' perceptions of using video and media PowerPoint with independent learning. This study implies that Islamic Religious Education Learning was very complex in increasing students' learning independence. As anticipation, a more precise learning process was needed.